Utilization of Adaptive Communication in End-Of-Life Care in Intensive Care Unit During the Covid-19 Pandemic: Literature Review - Ulfah Nurrahmani (Journal of Nursing Science Update (JNSU), 2022)
Covid-19 is becoming a global pandemic that presents new challenges in critical care. Visitation restrictions and isolation are major challenges in end-of-life care communication. The use of communication as an indicator of the quality of end-of-life care in the critical care management chain is required to adapt creatively and effectively. The aim of this research is to know the description of communication in end-of-life care in intensive care units during the covid-19 pandemic based on literature sources related to scientific research journals. The research was conducted by searching for research results published in 2019-2021 from databases such as PubMed, google scholar, and science direct using the keywords "communication", "end-of-life", "intensive care unit", and "pandemic". The search results selected twelve articles that met the PICO analysis for review. Twelve articles explain that adaptive communication can be carried out between patients, families, and the medical team through continuous video and telephone calls. Long-distance communication is carried out by following special rules, namely on time, coordinated by the entire team, and environmental and patient readiness, both in outward appearance and hemodynamic status. Communication adaptations in other forms are described in more detail in the communication guide checklist and written information sheets, as well as efforts to increase the role and number of nursing staff in large-scale communications. The use of adaptive communication positively can be beneficial in improving the quality of end-of-life care in intensive care units during a pandemic.